New Users of Antipsychotics Among Children and Adolescents in 2008–2017: A Nationwide Register Study - Varimo, Eveliina; Saastamoinen, Leena K.; Rättö, Hanna; Mogk, Hannu; Aronen, Eeva T. (Frontiers in Psychiatry, 2020)
INTRODUCTION: Recently, prescribing antipsychotics for children and adolescents has been increasing in many countries. These drugs are often prescribed off-label, although antipsychotics have been associated with adverse effects. We determined the recent incidence of antipsychotic use among children and adolescents in Finland. METHODS: Finnish National Prescription Register including all Finnish inhabitants receiving reimbursement for pharmaceuticals was searched for subjects of 1-17 years of age who had started an antipsychotic drug between 1 January 2008 and 31 December 2017 (n=26 353). Between 2008 and 2017, the range of number of Finnish children and adolescents aged 1-17 years was 1.01-1.03 million/year. The incidence was calculated by dividing the number of new users by all age- and sex-matched Finnish inhabitants in the year. RESULTS: Between 2008 and 2017, the incidence of antipsychotic use among children and adolescents increased from 2.1 to 3.8 per 1000 individuals, respectively. In children aged 7-12 years, the incidence of antipsychotic use 1.4-folded (from 1.9 (95% CI:1.8-2.0) to 2.7 (95% CI:2.5-2.9) per 1000) with a cumulative increase of 0.2% per year (χ2=51.0, p<0.0001). In adolescents aged 13-17 years, the incidence 2.2-folded (from 4.3 (95% CI:4.1-4.5) to 9.4 (95% CI:9.1-9.8) per 1000) with a cumulative increase of 0.6% per year (χ2=590.3, p<0.0001). The increase in the incidence of use was steeper in girls (2.3-fold) than in boys (1.4-fold) (χ2=85.6, p<0.0001), especially between 2015 and 2017 (1.6-fold and 1.2-fold, respectively) (χ2=151.7, p<0.0001). The year 2011 was the turning point when the incidence in girls exceeded the incidence in boys, and the incidence of quetiapine use exceeded that of risperidone use. CONCLUSIONS: The incidence of antipsychotic use increased between 2008 and 2017, especially in adolescent girls. The use of quetiapine increased, although it has few official indications in children and adolescents. Future studies should investigate the reasons for increasing use of antipsychotics, especially quetiapine, in children and adolescents.